Industry talk - Sorooshian, Shahryar; M., Waris; Senthil Kumar, T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (Faculty of Industrial Management, 2016)
In conjunction with the effort to increase graduate employability and expose student’s to industry’s real practice, Faculty of Industrial Management have organized an Industrial Talk titled “Go Beyond Logistics: Possibility in Every Direction”.